EFFECT OF DIFFERENT PLANTING DATES ON ANTHRACNOSE OF SORGHUM - REKHA; YOGENDRA SINGH (The Bioscan, 2015)
The main aim of this study was to investigate the effect of different sowing dates on the severities, infection rates and AUDPC of Sorghum anthracnose, caused by Colletotrichum graminicola on two varieties of Sorghum (Sorghum bicolor L., Moench). The varieties were: PC-6 and MP- Chari.The investigations were undertaken during 2009-10 and 2010 -11 cropping seasons at Livestock research centre, G.B.P.U.A &T Pantnagar. The experimental trial was laid out in split-split plots, arranged in a randomized complete block design withthree replications.The results obtained showed thatEarly planted (1st July) PC-6 and MP –Chari had higher disease severity and infection rate than late planted (30th July) sorghum cultivars.Plant grown from seed sown on the first sowing date (1stJuly) had significantly higher grain yield. Early planted PC-6 and MP Chari cultivars appeared to increase anthracnose disease. This study revealed that both cultivars could be planted between medium 20th&30th July for less disease severity and maximum grain yield.